Pengembangan Progam Muhadatsah Usbu’iyyah di Pondok Pesantren As-Sakienah Sliyeg Indramayu - Rohmawan Rohmawan; Hasan Saefuloh; Durtam Durtam (EL-IBTIKAR: Jurnal Pendidikan Bahasa Arab, 2021)
This study aims to determine the development of the usbu'iyyah muhadatsah program at the As-Sakienah Islamic Boarding School, Sliyeg-Indramayu. Pondok Pesantren As-Sakienah Sliyeg-Indramayu, is one of the institutions that implements a linguistic environment and has been applied for a long time. Students, teachers and society in it must speak Arabic every day. It also includes language activities to help them speak Arabic, such as Muhadloroh, speeches, speeches, and language festivals. And they have to get used to speaking Arabic in this environment. This research is an R&D (Research and Development) research. The results of this study: 1). The teaching curriculum at the As-Sakienah Islamic Boarding School Sliyeg-Indramayu uses two languages, namely Arabic and English, and this is one of the causes of the shortage and decline in teaching performance of the weekly Arabic conversation program. 2). The researcher concludes that the purpose of teaching speaking skills is to learn Arabic sounds and dialect sounds and the like, and to express their thoughts using the correct word formation system in Arabic, especially in Arabic. spoken language, as well as to familiarize students with the rules of speaking, listening and paying attention to the words of the person speaking For some of them, even if they do not agree with him in opinion and perseverance. 3) The aim of the weekly Arabic conversation teaching program at the As-Sakienah Islamic Boarding School, Sliyeg-Indramayu, is that students can learn everyday speech in foreign languages, especially Arabic. By adding foreign Arabic conversations each week, teacher students can speak the language and create a linguistic environment in the institution. And then we create a calendar on this additional conversation.